The Preeclampsia Screening Method Using MAP and ROT in Third Trimester Pregnant Women - INTAN KARLINA; Diani Aliansy; Yuyun Yunengsih (Universitas Muhammadiyah Pekajangan Pekalongan, 2023)
Preeclampsia can contribute to a direct impact on the mother and fetus. Various problems that can threaten the life of a mother with preeclampsia. There is a need for routine antenatal care assistance and examinations by conducting Mean Artery Pressure (MAP) and Roll Over Test (ROT) examinations. The aim of this study was to identify two screening methods which one was more effective in detecting preeclampsia so that initial treatment of mothers with abnormally elevated blood pressure could minimize complications that might occur. Methods: The study was the prevalence ratio with cross sectional approach by assessing the association between Mean Artery Pressure and Roll Over Test as a preeclampsia screening method. The population were 62 respondents. The sample of 54 respondents were obtained in this study with accidental sampling technique. The instrument used an observation sheet. Univariate analysis was used for identifying frequency distribution and bivariate analysis with chi square test. Results: Less than half of preeclampsia screening with the MAP method in third trimester pregnant women with a positive result of 40.7%. Less than half of preeclampsia screening with the ROT method in third trimester pregnant women with a positive result of 38.9%. Less than half of third trimester pregnant women experience preeclampsia by 25.9%. There was a relationship between the MAP screening method and a p-value of 0.001 (<0.05) and a prevalence ratio of 2.022. There was a relationship between the ROT screening method and a p-value of 0.004 (<0.05) and a prevalence ratio of 1.152. The most influential screening method in detecting preeclampsia was the MAP method with an RR value of 11.694, meaning that the MAP method was 11.694 greater in detecting preeclampsia, while the ROT method was 5.067 in detecting preeclampsia. Conclusion: The most influential screening method in detecting preeclampsia was the MAP method